PELAYANAN PASIEN RAWAT INAP KELAS III DI RUMAH SAKIT UMUM YARSI PONTIANAK - S. Aminah Herlinah E.21109084 (FISIP Universitas Tanjungpura, 2013)
The problem in this study is the absence of kesingkronan in directing the procedure so as to make them confused. Where also the medical officer in answering questions that ask patients still less politely, is evident from the way they talk to paasien always with a harsh tone or on leave granted, especially a senior nurse. While in treating patients because there is still injustice still view the economic status of the patient / care classes, it is evident from the different treatment between class III and class VIP, VIP If patients need help is always fast response, whereas for class III is often overlooked. The results showed that the attitude of nurse involvement in providing health care to patients in Class III Inpatient General Hospital YARSI Pontianak, still considered unsatisfactory for patients / the public, since neither the speed nor the initiative in providing the service is still not up and away from the expectations of society . Addressing the phenomenon that is the authors provide recommendations for services provided to conform with what the expectations of the people, then the hospital needs to pay attention to the availability of the existing workforce, so the nurse will be able to work with the maximum.Keywords: Full Involment, Quick Response, Emphati to patien, Sesiousness.